Qualidade da água e comunidades de diatomáceas epilíticas na bacia hidrográfica do rio Vacacaí, Santa Maria, Rio Grande do Sul - Durigon, Mariana (2013)
The main aim of this study was to analyze the composition and structure of the diatom community (Bacillariophyceae) in the River Vacacaí hydrographic basin, Santa Maria municipal district, state of Rio Grande do Sul, Brazil, and its relation to physical and chemical variables, related to water quality. Monthly field trips were carried out between June 2011 and July 2012 in six sampling stations along the river course, in order to collect epilithic diatoms in natural substrates as well as water samples. Qualitative and quantitative analyses of the communities were performed on permanent glass slides under a light microscope. The relative abundance of diatom species was obtained from the count of at least 600 valves on each slide, as well as identification of taxa to species and variety levels. The following water quality variables were also measured: biochemical oxygen demand (BOD), chemical oxygen demand (COD), pH, suspended solids (SS), conductivity, turbidity, and dissolved oxygen. The results were compared to the water use categories determined by the National Council for the Environment (CONAMA) in a resolution issued in 2005. Multivariate techniques (cluster, canonical correspondence and indicator species analyses) and community structure parameters (species richness, Shannon‟s Diversity Index, determination of abundant and dominant species in each sample) were used in order to describe environmental and biological patterns found. 171 species were identified in total. Multivariate analyses resulted in grouping of the sampling stations rather than sampling dates, with the upstream sections separated from the downstream zones. The latter were characterized by higher values of BOD, COD and conductivity, as well as the dominance of diatoms species typical of pollutes sites such as Sellaphora pupula, Nitzschia palea, Gomphonema parvulum and Cocconeis placentula. At the most polluted site, species richness and diversity indices were significantly lower than at the remaining sampling stations. Human activities, markedly sewage effluents are pointed as the main causes of water quality degradation.